An overview of the Fe-chalcogenide superconductors. (10th July 2015) - Wu, M K; Wu, P M; Wen, Y C; Wang, M J; Lin, P H; Lee, W C; Chen, T K; Chang, C C
Abstract: This review intends to summarize recent advancements in FeSe and related systems. The FeSe and related superconductors are currently receiving considerable attention for the high critical temperature ( T C ) observed and for many similar features to the high T C cuprate superconductors. These similarities suggest that understanding the FeSe-based compounds could potentially help our understanding of the cuprates. We begin the review by presenting common features observed in the FeSe- and FeAs-based systems. Then we discuss the importance of careful control of the material preparation allowing for a systematic structure characterization. With this control, numerous rich phases have been observed. Importantly, we suggest that the Fe-vacancy ordered phases found in the FeSe-based compounds, which are non-superconducting magnetic Mott insulators, are the parent compounds of the superconductors. Superconductivity can emerge from the parent phases by disordering the Fe vacancy order, often by a simple annealing treatment. Then we review physical properties of the Fe chalcogenides, specifically the optical properties and angle-resolved photoemission spectroscopy (ARPES) results. From the literature, strong evidence points to the existence of orbital modification accompanied by a gap-opening, prior to the structural phase transition, which is closely related to the occurrence of superconductivity. Furthermore, strong lattice to spin coupling are important for the occurrence of superconductivity in FeSe. Therefore, it is believed that the iron selenides and related compounds will provide essential information to understand the origin of superconductivity in the iron-based superconductors, and possibly the superconducting cuprates.